Exit speed score and serum lactate can be used as tools to assess improved cattle handling practices - Lima, Maria Lúcia Pereira; Negrão, João Alberto; de Paz, Claudia Cristina Paro; Trindade, Pedro Henrique Esteves [UNESP]; Grandin, Temple (My University, 2018)
This experiment was conducted to investigate the use of serum lactate to evaluate the quality of cattle handlings. Blood cortisol and lactate levels in Nellore steers were compared when they were handled in both the traditional way and after the introduction of calm handling methods and simple corral modifications. People using traditional methods yelled, hit cattle, and used both dogs and electric prods. The corral modifications consisted of blocking the vision of the steers when the handler stands inside the animal’s flight zone, eliminating contrast of light and dark or shadows and puddles. During calm handling, the stockperson was asked to be calm and not allowed to scream or hit the animals. Electric cattle prods or dogs inside the corral were not allowed. A total of 382 Nellore steers aged 14 to 20 months from five different ranches were studied. In the first evaluation, the behavior of the animals was evaluated and blood samples were collected after traditional handling. After corral modification and the introduction of calm handling procedures, the same animals returned (6 days later) for a second assessment and blood collection from the jugular vein for serum cortisol determination. The animals were evaluated using visual scores. Entry behavior (EB) into the restraint device was evaluated by observing whether the steers walked, trotted, or ran. Chute temperament (CT) was assessed by determining whether the animal was very calm, calm, agitated, very agitated or struggling to escape. Exit speed (ES) was evaluated with scoring of walk, trot or run. After both corral and handling modifications, the animals exhibited lower EB (P < 0.01), CT (P < 0.01), and ES (P < 0.01). Serum cortisol (P < 0.01) and lactate (P = 0.03) were significantly lower after the improvements. Mean serum cortisol was 47.87 vs 32.49 mg/dL, and lactate was 37.08 vs 33.65 mg/dL before and after corral and handling modifications, respectively. Lactate levels and exit speed are strongly related. Both exit speed score and serum lactate may be good tools to evaluate the quality of handling.
Keywords: Cattle stress; Exit velocity; Handling welfare